2005
DOI: 10.1590/s0104-66322005000300001
|View full text |Cite
|
Sign up to set email alerts
|

Purification of recombinant aprotinin produced in transgenic corn seed: separation from CTI utilizing ion-exchange chromatography

Abstract: -Protein expression in transgenic plants is considered one of the most promising approaches for producing pharmaceutical proteins. As has happened with other recombinant protein production schemes, the downstream processing (dsp) of these proteins produced in plants is key to the technical and economic success of large-scale applications. Since dsp of proteins produced transgenically in plants has not been extensively studied, it is necessary to broaden the investigation in this field in order to more precisel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Overall, few detailed protocols for downstream processing have been published. Azzoni et al (2005) showed that replacing immobilized metal affinity chromatography (IMAC) with a cation exchange chromatography step achieved a tenfold improvement in the recovery and purity of recombinant aprotinin from transgenic maize. Similarly, Nandi et al (2005) showed that lactoferrin was efficiently extracted from rice flour in phosphate buffer (pH 7.0) containing up to 0.5 M NaCl.…”
Section: Downstream Processing and Purificationmentioning
confidence: 99%
“…Overall, few detailed protocols for downstream processing have been published. Azzoni et al (2005) showed that replacing immobilized metal affinity chromatography (IMAC) with a cation exchange chromatography step achieved a tenfold improvement in the recovery and purity of recombinant aprotinin from transgenic maize. Similarly, Nandi et al (2005) showed that lactoferrin was efficiently extracted from rice flour in phosphate buffer (pH 7.0) containing up to 0.5 M NaCl.…”
Section: Downstream Processing and Purificationmentioning
confidence: 99%
“…The peptide extracts were allowed to pass through cation and anion exchange resin columns (Dowex 50 and Dowex 1, Sigma Chemical Co., USA) (Azzoni et al, 2005). 3N ammonia and 1N HCl was used for cation and anion exchange column respectively during peptide elution procedure.…”
Section: Ion Exchange Chromatographymentioning
confidence: 99%
“…The purification workhorse for many protein separation processes, including those published for purifying recombinant proteins from plants,19–21 is selective adsorption and elution of the target molecule using a packed bed of porous resin beads containing specific adsorptive ligands (i.e., ion exchange, hydrophobic, or affinity) 22, 23. The operation provides excellent purification factors, is reliably scaled between development and manufacturing sizes, and can be easily validated for commercial production 24.…”
Section: Introductionmentioning
confidence: 99%